Development of Competitive Relations in the Russian Market of Educational Services - Ivinskaya, Elena Y.; Nikitin, Aleksandr A.; Markovichev, Aleksandr S.; Sinenko, Vasily Y.; Mavrina, Irina A.; Zhafyarov, Akram Z.; Milinis, Olga A.; Zhukov, Gennady N. (International Review of Management and Marketing, 2016)
The transition of Russia to a market economy rose scientific interest to the issues of competitiveness of Russian higher education; and as a consequence there was a need of theoretical analysis of accumulated domestic and foreign experience. This article aims at identifying of the peculiarities of competitive relations in the market of educational services and the development of practical recommendations for the entities of economic relations. The article identifies the need to develop a marketing strategy for educational institutions based on the mechanisms of competitive behavior in the market of educational services in the region. Basic directions of competitive activities are revealed and the emergence of hyper-competition is proved in the market of educational services due to the cumulative impacts of previously isolated from each other competitive factors. The authors propose a classification and mechanisms of implementation of the marketing competitive strategy of educational organizations, depending on its type. This article is intended for the heads of educational institutions, senior managers, researchers involved in the development of the education market and competitiveness of educational institutions. Keywords: educational services, educational institutions, competitiveness, marketing strategies JEL Classifications: A23, I23, I26